2021
DOI: 10.3390/genes12071061
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of SARS-CoV-2 Variants on Deaths, Case Incidence and Case Fatality Ratio among the Continents for the Period of 1 December 2020 to 15 March 2021

Abstract: The outbreak of coronavirus disease 2019 (COVID-19), by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has quickly developed into a worldwide pandemic. Mutations in the SARS-CoV-2 genome may affect various aspects of the disease including fatality ratio. In this study, 553,518 SARS-CoV-2 genome sequences isolated from patients from continents for the period 1 December 2020 to 15 March 2021 were comprehensively analyzed and a total of 82 mutations were identified concerning the reference sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…As regards the data on nsp3, the Q180H and N1329D mutations were identified at a low frequency (2.59%) in Italian genomes of the BF.7 lineage. In particular, literature data showed that the frequency of the Q180H mutation ranged from 0.05% to 1.18% in SARS-CoV-2 genomes collected in Africa, Asia, Australia, Europe, North America, and South America [31,32]. The same authors identified the mutation Q180H with a significant negative correlation with a case fatality ratio.…”
Section: Discussionmentioning
confidence: 91%
“…As regards the data on nsp3, the Q180H and N1329D mutations were identified at a low frequency (2.59%) in Italian genomes of the BF.7 lineage. In particular, literature data showed that the frequency of the Q180H mutation ranged from 0.05% to 1.18% in SARS-CoV-2 genomes collected in Africa, Asia, Australia, Europe, North America, and South America [31,32]. The same authors identified the mutation Q180H with a significant negative correlation with a case fatality ratio.…”
Section: Discussionmentioning
confidence: 91%
“…Due to the occasional presence of a gradual escalation in epithelial changes in adjacent areas even in the same sample, diagnostic entities were grouped as following: epithelial hyperplasia-to-mild dysplasia and moderate-tosevere dysplasia. As the SARS-CoV-2 is primarily a virus of the respiratory tract [1][2][3], we included samples of upper respiratory mucosa (nose and maxillary sinus), collected from cases of inflammatory conditions, which served as controls. All cases comprised of tissues that were referred to the oral pathology laboratory before the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was first reported in December 2019 in Wuhan, China, was found to be responsible for the coronavirus disease 2019 (COVID-19) that became a worldwide pandemic [1]. This is an enveloped single stranded RNA virus with a complete genome of about 30,000 nucleotides, that translates both structural and non-structural proteins [2].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has been recorded in most countries of the world, with noticed high transmission and morbidity rates that triggered the alarm for public health to respond to emerging diseases [ 5 ]. The World Health Organization (WHO) declared the COVID-19 outbreak a worldwide pandemic on 11 March 2020.…”
Section: Introductionmentioning
confidence: 99%